KONTRIBUSI POWER OTOT LENGAN DAN OTOT TUNGKAI DENGAN HASIL TOLAK PELURU MAHASISWA PROGRAM STUDI PENDIDIKAN KEPELATIHAN OLAHRAGA FKIP UNIVERSITAS RIAU - Ni Putu Nita Wijayanti, dkk (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2014)
Problem in the research was started from observation that the author encountered in the field. It turned out the implementation of the O’Brien shot-put movement of second semester students at Sports Coaching Education Riau University was still a lot of lack such that students’ shooting was not so optimal which was allegedly influenced by powerful arm and leg muscles. The purpose of this research was to find the contribution of powerful arm and leg muscles to the shot-put result of second semester students at Sports Coaching Education Riau University. The research method was correlation. The population in this research was 78 second semester students of Sports Coaching Education Riau University using purposive sampling technique. The sample on this research was defined as many as 45 male students who had passed the O’Brien shot-put style. To get the data researchers used a shot-put test, standing broad jump and the O’Brien shot-put result. The data were analyzed with product moment and coefficients of determinant for determining contributions. Based on the analysis of the data it was found that there was a significant relationship between the powerful arm muscles and the shot-put result obtained r.count 0,257 > r.table 0,294 with contributions amount 9,36%, then there was a significant relationship between the powerful leg muscles and shot-put result, obtained r.count 0,816 > r.table 0,294 with contributions amount 66,59%, and there was also a significant relationship between the powerful arm and leg muscles and the O’Brien shot-put result second semester students at Sports Coaching Education Riau University, obtained r.count 0,819 > r.table 0,294 with contributions amount 67,07%.